Pengaruh Pencahayaan terhadap Kinerja Segmentasi - Kartowisatro, Iman H. (Bina Nusantara University, 2014)
Light intensity may affect the image quality of an object that can cause barriers in doing preprocessing to improve the image quality of a digital image. Furthermore, this would also be an impact on subsequent processes, such as sorting images according to the needs. Light intensity influences the reflection of light which translates into an image. This gives an impact on successful segmentation process. Examples of the success and failure of segmentation are presented in this paper.